Everyday Walking Among Older Adults and the Neighborhood Built Environment: A Comparison Between Two Cities in North America - Herbolsheimer, Florian; Mahmood, Atiya; Michael, Yvonne L.; Chaudhury, Habib (Frontiers in Public Health, 2020)
A walkable neighborhood becomes particularly important for older adults for whom physical activity and active transportation are critical for healthy aging-in-place. For many older adults, regular walking takes place in the neighborhood and is the primary mode of mobility. This study took place in eight neighborhoods in Metro Portland (USA) and Metro Vancouver (Canada), examining older adults' walking behavior and neighborhood built environmental features. Older adults reported walking for recreation and transport in a cross-sectional telephone survey. Information on physical activity was combined with audits of 355 street segments using the Senior Walking Environmental Audit Tool-Revised (SWEAT-R). Multi-level regression models examined the relationship between built environmental characteristics and walking for transport or recreation. Older adults [N = 434, mean age: 71.6 (SD = 8.1)] walked more for transport in high-density neighborhoods and in Metro Vancouver compared to Metro Portland (M = 12.8 vs. M = 2.2 min/day; p < 0.001). No relationship was found between population density and walking for recreation. Older adults spent more time walking for transport if pedestrian crossing were present (p = 0.037) and if parks or outdoor fitness amenities were available (p = 0.022). The immediate neighborhood built environment supports walking for transport in older adults. Comparing two similar metropolitan areas highlighted that high population density is necessary, yet not a sufficient condition for walking in the neighborhood.